ANALYSIS OF THE MECHANICS OF DIE DRAWING POLYPROPYLENE THROUGH STRAIN-RATE CONTROLLED DIES - ULAS, I; CRAGGS, G (MECHANICAL ENG PUBL LTD, 1995)
The die drawing of polymers in the solid state is now an established process for achieving molecular orientation in drawn products and an enhancement of their mechanical properties. A mechanics analysis is presented of the drawing of polypropylene through strain rate controlled dies, where the strain rate is either constant, increasing at a uniform rate or decreasing through the die. The stress in an element of material being drawn is determined from equilibrium considerations and application of the Tresca yield criterion. Flow stress data are deduced from uniaxial stress-strain-strain rate tests and applied to the problem using equivalent stress-strain concepts. Results are presented of axial stress, flow stress and die wall pressure throughout the dies and show that polypropylene can prematurely leave contact with the die wall, particularly in decreasing strain rate dies at high drawing speeds. Increased friction of the die wall and increased drawing speed cause this 'loss of contact' point to move progressively downstream in all die cases. Theoretically predicted drawing loads show acceptable agreement with experimental test results when low values of friction coefficient are assumed.
Keywords: DIE DRAWING PROCESS; POLYPROPYLENE; STRAIN RATE CONTROLLED DIES; EQUILIBRIUM; TRESCA YIELD CRITERION; POLYMERS; RODS; Engineering